Some integer partitions induced by orbits of dynkin type (2017)
ABSTRACT: A categorification in the sense of Ringel and Fahr is given to the sequences A016116 and A000034 in the OEIS by using τ-orbits in the Auslander-Reiten quiver of some Dynkin algebras.